Pemberian Pisang Ambon (Musa paradisiaca var. Sapientum) dan Penurunan Tekanan Darah Sistolik Diastolik Penderita Hipertensi - Parameswari, Anggun; Prihatin, Setyo; Sunarto, Sunarto (Poltekkes Kemenkes Semarang, 2014)
Background: Hypertension is a serious public health problem andmajor risk factor for cardiovascular disease. High consumption of potassium decrease blood pressure. One of food which contains potassium is Musa paradisiaca var.sapientum.Objective: To find out the effect of Musa paradisiaca var. sapientum on systolic and diastolic blood pressure in hypertension patients.Method: This was an experimental study which used randomized pre test - post test control group design conducted in Wonosoco, Kudus, involving twenty patients hypertension with systolic blood pressure 140-159 mmHg and diastolic 90-99 mmHg. Subjects were divided into two groups. The first group was a treatment received 300 grams of Musa paradisiaca var.sapientum containing 1305 mg of potassium for 5 days. The second group was a control received standart treatment.Results: Systolic and diastolic blood pressure decrease of 25,50 mmHg and 17,00 mmHg in treatment group, and decrease of 11,00mmHg and 6,00 mmHg in control group. There were difference in systolic and diastolic blood pressure before and after treatment (p<0,05). There were significant difference in systolic and diastolic blood pressure at post-test between two groups controlled by of potassium and sodium intake (p<0,05).Conclusion: Musa paradisiaca var. sapientum decreases of systolic and diastolic blood pressure in hypertension patients.